Development of hybrid antibacterial membrane by incorporating silver particle with 2,4,6-triaminopyrimidine as compatibilizer - Basri, Hatijah (2012)
The objective of this study was to develop and characterize the polyethersulfone (PES) incorporated with silver (Ag) as an antibacterial membrane which can remove and disinfect bacteria in a single step for environmental application. The PES-Ag membrane was developed from PES, silver nitrate as an antibacterial agent and 2,4,6-triaminopyrimidine (TAP) as compatibilizer. The influence of AgNO3 loading, molecular weights (MW) of polyvinylpyrrolidone (PVP) as dispersant and type of compatibilizer have been investigated. The resulting membranes were characterized based on their thermal, tensile and structural properties which were used in correlation with the membrane antibacterial properties. The incorporation of Ag in PES membrane has increased the tensile strength doubled as compared to the unmodified PES. Furthermore, it was observed that the highest AgNO3 loading (2 wt%) and the highest MW (360,000) of PVP as dispersant has led to higher silver content on membrane surfaces. This is evidenced from energy dispersive X-ray (EDX) analysis and X-ray photoelectron spectroscopy (XPS). These properties have induced a better antibacterial activity in a disc-diffusion test against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus). The structural characterization by field emission scanning electron microscope (FESEM) revealed that by incorporating TAP as compatibilizer, smaller Ag particles size with improved distribution and average pore size of 0.174 µm was obtained. In addition, the silver residue during fabrication monitored by inductive coupled plasma-mass spectrometry (ICP-MS) was significantly reduced (62.6%). These parameters have led to E.coli removal of log reduction value (LRV) 3.59 and 100% growth inhibition tested on E.coli suspension of 1×106 colony forming unit (CFU/mL). From the adhesion test, this membrane exhibited the least E.coli adherence which in turn evidenced its antiadhesion property. In conclusion, the PES-Ag membrane with TAP as compatibilizer produced was potential in bacteria removal and disinfection below the CFU maximum range for water and waste water treatment.